2015
DOI: 10.11591/.v4i3.4725
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Air Contamination in an Intensive Care Unit

Abstract: Unit layout affects every aspect of intensive care services, including patient safety. A previous study has shown that patients admitted to beds adjacent to the sink and to the door of a large bayroom had the highest number of positive blood cultures and the highest blood culture incidence density, respectively. The present study measures microbial air contamination in a medical intensive care unit of a medical center in central Taiwan. Of the 17 rooms, 8 rooms with distinct physical environmental characterist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 7 publications
0
3
0
3
Order By: Relevance
“…as the most frequent fungi. Chang et al, (2015) also reported that the fungal concentrations for different locations in Intensive Care Unit in Taiwan did not reach statistical significance and generally were in the standards.…”
Section: Resultsmentioning
confidence: 98%
“…as the most frequent fungi. Chang et al, (2015) also reported that the fungal concentrations for different locations in Intensive Care Unit in Taiwan did not reach statistical significance and generally were in the standards.…”
Section: Resultsmentioning
confidence: 98%
“…This importance of the site is supported by a study performed in Taiwan in 2015 where a significant difference was found in bacterial concentration in different sites where highest concentration was found in rooms at the front end of the circulation. Thus we could conclude the most beneficial sites where air filter should be located and sites to be more taken care of to minimize susceptibility of patient infection (7) .…”
Section: Discussionmentioning
confidence: 97%
“…Para cuantificar la carga microbiana en el aire, existen actualmente el método pasivo y el método activo; en ambos métodos se procede al conteo de las ufc, ya sea de bacterias y/o hongos 6 . En este estudio se empleó el método activo puesto que es el recomendado por el Instituto de Salud Pública de Chile 8 . Los recuentos máximos de bacterias y hongos, determinados en el aire al interior del CECOSF-Centinela en Talcahuano, Región del Biobío, variaron entre 2.376-775 ufc/m 3 para bacterias y 153-61 ufc/m 3 , para los hongos.…”
Section: Discussionunclassified
“…Durante julio de 2018 hasta junio de 2019 se tomaron muestra de aire en seis áreas del CECOSF-Centinela en Talcahuano, Región del Biobío. El muestreo se realizó cada 15 días de manera activa empleando el equipo MAS-100 NT (Merck, Alemania, nº de serie: 15986), equipo recomendado en la norma chilena para el estudio de calidad microbiológica de aire 8 . El equipo se dispuso en el centro de cada sala a una altura de 1 m y se programó para filtrar 250 L de aire a un flujo de 100 L/min.…”
Section: Procedimiento De Muestreo De Aireunclassified
See 1 more Smart Citation